-9(1+r)=36

Simple and best practice solution for -9(1+r)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(1+r)=36 equation:


Simplifying
-9(1 + r) = 36
(1 * -9 + r * -9) = 36
(-9 + -9r) = 36

Solving
-9 + -9r = 36

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -9r = 36 + 9

Combine like terms: -9 + 9 = 0
0 + -9r = 36 + 9
-9r = 36 + 9

Combine like terms: 36 + 9 = 45
-9r = 45

Divide each side by '-9'.
r = -5

Simplifying
r = -5

See similar equations:

| 0(0x+1)-5=10 | | 90-4t=25(180-t) | | y-1/4=-3/5 | | 4n+5n=-18 | | 333-112/4 | | 3x-19=-x-2(1-2) | | x+(-53)=89 | | t/0.5=15/ | | y-5/9=-6 | | 3x+2y=2y+3x | | 7/9r+28=-28 | | -12=5a-a | | (8.50x10^6)/(2x10^3) | | 9(x+2)+2=-34 | | 13x+9+4y+2=180 | | 9n-6=8n+7 | | 4-m/2=20 | | 3x-x-10=90 | | 2-15n=5(-3+z) | | -3x^2+24x-45=0 | | -3(-2x+1)-5=10 | | 15=6x-3x | | 3(x-4)+6=2x | | 3(q-5)=4a-(2a+4) | | 9(2K+3)+2=11(11K-11K) | | X-3x-10=90 | | x/6+14=0 | | 2x+7(2x-16)=48 | | 2x+7=-2x+5 | | 5r-18r-6=111 | | 6=-7/9+v | | 33333333n=33333333 |

Equations solver categories